HUBUNGAN ANTARA PENERAPAN PERMAINAN ROUND OF DRAGON SNAKE RAINBOW DENGAN PENINGKATAN KETERAMPILAN SOSIAL PESERTA DIDIK - Jumiati; Permata Sari, Nina; Qomario (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social skills are an important competency that students need to possess to support social interaction, self-adjustment, and success in the learning process. However, the results of a preliminary study at SMP Negeri 30 Banjarmasin indicate that students' social skills remain suboptimal, as reflected in low levels of communication, cooperation, empathy, and self-control. One alternative medium for Guidance and Counseling services that can be used to help develop social skills is the Round of Dragon Snake Rainbow (RoDSR) game. This study aims to determine the relationship between the implementation of the RoDSR game and students' social skills at SMP Negeri 30 Banjarmasin, using a quantitative approach with a correlational design. The research sample consisted of 59 seventh-grade students selected through purposive sampling technique. Data were collected using a questionnaire on the implementation of the RoDSR game and a social skills questionnaire, both of which had met the requirements of validity and reliability testing. Data analysis was conducted using the Kolmogorov-Smirnov normality test and Spearman Rank correlation test with the assistance of IBM SPSS Statistics version 25.0. The results showed a positive and significant relationship between the implementation of the RoDSR game and students' social skills, as indicated by a significance value of 0.000 (p < 0.05) and a correlation coefficient of 0.675, which falls into the strong category. These findings suggest that the better the implementation of the RoDSR game, the better students' social skills tend to be. Thus, the RoDSR game can serve as an alternative medium for Guidance and Counseling services to support the development of students' social skills.